Fourth Five Year Plan Andaman and Nicobar Islands - Planning Commission (Planning Commission, 1969)
Training camps will be organised for farmers to emphasise the importance of intensive cultivation of agricultural and Horticultural crops. 1000 farmers will be covered under the short-term training course of 3-4 days duration and another 2000 farmers through production-cum-demonstration camps.
Andaman and Nicobar Administration
Andaman and Nicobar Administration